A SURVEY OF ENGLISH DEPARTMENT STUDENT’S READING STRATEGY IN READING ACADEMIC ARTICLES - Ferdinandus, Marcy S; Simantuak, Jamaludin (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2024)
This study aims to find out the students’ strategies in reading academic articles, explain the student’s problems in reading academic articles and describe the ways the students used to solve the problems of students at the English Study Program of Pattimura University. The survey design and the quantitative method were used as the method in this study. The data was collected using a questionnaire and an In-depth Interview. The results showed that the students of the English Department mostly used the use of reading strategies when reading academic articles. The three categories of reading strategies GLOB, PROB and SUPP Strategies help the students when they are challenged to read academic articles. Furthermore, the students can improve their critical thinking when they use those strategies. The problems that the students faced when reading academic articles were they found unfamiliar words or phrases, and difficulty in covering the related ideas in the text and the content of the text. Poor vocabulary is the most problematic in reading academic articles. The way the students solved their problems was by guessing the meaning from context, using dictionaries, highlighting, scanning and skimming and mind mapping. Respondents agreed that using a dictionary or Google Translator as the alternative provided in these strategies can solve or handle the difficulties in the articles. They also said that without using these strategies when reading academic articles, can make them lose their concentration to understand the texts. Therefore, the results of this study provide insight for English students to make the correlation between their reading strategies and writing ability to make their critical review paper when reading academic articles.